Creating Culturally-Safe Schools for Māori Students - Macfarlane, Angus; Glynn, Ted; Cavanagh, Tom; Bateman, Sonja (The Australian Journal of Indigenous Education, 2007)
Abstract In order to better understand the present trends in New Zealand’s schooling contexts, there is a clarion call for educators to develop sensitivity and sensibility towards the cultural backgrounds and experiences of Maori students. This paper reports on the work of four scholars who share research that has been undertaken in educational settings with high numbers of Maori students, and discusses the importance of creating culturally-safe schools - places that allow and enable students to be who and what they are. The theoretical frameworks drawn on are based on both a life partnership analogy as well as on a socio-cultural perspective on human development and learning. The Maori worldview presented in this paper is connected to the Treaty of Waitangi, The Educultural Wheel and the Hikairo Rationale. Data were collected from two ethnographic case studies and analysed through these frameworks. Practical suggestions are then made for using restorative practices and creating reciprocal relationships in classrooms within an environment of care. The paper reports on an evidence-based approach to creating culturally-safe schools for Maori students.